PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BAGIAN RUMAH TANGGA DAN PERBEKALAN UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA - Bambang Tri Pamungkas (Program Studi Manajemen, 2020)
This study aims to determine whether there is a partial influence of work environment and motivation on the performance of Sarjanawiyata Tamansiswa Yogyakarta Household Employees. To find out the influence of work environment and work motivation simultaneously on the performance of Sarjanawiyata Tamansiswa Yogyakarta Household Employees. The nature of this research is correlational. The variables of this study are the work environment and work motivation and employee performance. The population in this study were all Household Employees at the University of Sarjanawiyata Tamansiswa Yogyakarta with a population of 37, a population of less than 100, so that all populations were sampled by the census method. The data collection method uses a questionnaire. The analysis technique used is multiple linear regression with a significance level of 5%. The results obtained by the work environment has a positive and significant effect on the performance of employees of the Household Section of the Sarjanawiyata Tamansiswa Yogyakarta University. Work motivation has a positive and significant effect on the performance of employees of the Household Section of the Sarjanawiyata Tamansiswa University in Yogyakarta. Employee performance is influenced by the work environment and work motivation by 29.3%, while the remaining 70.7% is influenced by other factors.